Aguti e bambole. Il palco ligneo della casa di Bartolomeo Scala a Firenze - Belli, Gianluca (Opus Incertum, 2018)
The information on the construction of the Florentine house of Bartolomeo Scala, a building attributed with excellent reasons to Giuliano da Sangallo, has increased thanks to the discovery, three decades ago, of a book of accounts with a long series of expenses related to the works carried out from 1474 to 1477. The register has been linked to the work of Giuliano in the house, but almost certainly concerns an earlier phase, in which the existing buildings on the land plot purchased by Scala were reunited and adapted. In addition to providing names of masters and suppliers, the register contains many references to building materials, among which stand out many varieties of nails and a series of mirrors, used for the construction of the wooden “palco” of the hall. The analytical reading of this document allows us to hypothesize the form and characteristics of this extraordinary ceiling, perhaps decorated in such a way as to allude to the civic virtues of Bartolomeo Scala; in the text the position of the hall is also hypothesized, a room that has disappeared and has never been discussed before.